2017
DOI: 10.1016/j.bjm.2016.09.013
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Vibrio cholerae isolates from 1976 to 2013 in Shandong Province, China

Abstract: Cholera continues to be a serious public health issue in developing countries. We analyzed the epidemiological data of cholera from 1976 to 2013 in Shandong Province, an eastern coastal area of China. A total of 250 Vibrio cholerae isolates were selected for PCR analysis of virulence genes and pulsed-field gel electrophoresis (PFGE). The analysis of the virulence genes showed that the positive rates for tcpA and tcpI were the highest among strains from the southwest region, which had the highest incidence rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 22 publications
1
6
0
1
Order By: Relevance
“…37,38 Serotype conversion in endemic strains has been linked to environmental factors and immune pressure within the population. [38][39][40] The results of the phenotypic and genetic characterization reveal that earlier strains isolated in Kenya from 1975 to 1984 had typical El Tor characters, which is in agreement with previous studies done in Kenya. 32 Cholera outbreaks occurring between 2007 and 2017 were caused by new variants of V. cholerae O1 that had traits of both the classical and El Tor biotypes and were classified as hybrid type, El Tor variants, or unclassified (for those that did not fit in any category).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…37,38 Serotype conversion in endemic strains has been linked to environmental factors and immune pressure within the population. [38][39][40] The results of the phenotypic and genetic characterization reveal that earlier strains isolated in Kenya from 1975 to 1984 had typical El Tor characters, which is in agreement with previous studies done in Kenya. 32 Cholera outbreaks occurring between 2007 and 2017 were caused by new variants of V. cholerae O1 that had traits of both the classical and El Tor biotypes and were classified as hybrid type, El Tor variants, or unclassified (for those that did not fit in any category).…”
Section: Discussionsupporting
confidence: 86%
“…It has been attributed to a change in the genetic make‐up of the wbtT gene that determines the Ogawa specificity . Serotype conversion in endemic strains has been linked to environmental factors and immune pressure within the population …”
Section: Discussionmentioning
confidence: 99%
“…In this study, the established ERIC-PCR condition generated the amplicons mainly ranged from 100 to 5000 bp in size. Moreover, in this study, the 400 V. cholerae isolates were differentiated into 328 ERIC-genotypes (82.0%), which was more than 179 pulsotypes (71.6%) from 250 V. cholerae isolates, and 218 pulsotypes (38.4%) from 568 V. cholerae isolates based on Not I-PFGE (pulsed-field gel electrophoresis) genotyping technique (Gu et al 2014; Lu et al 2017). These data demonstrated the considerable genetic diversity of the 400 V. cholerae isolates recovered from the four freshwater fish species.…”
Section: Discussionmentioning
confidence: 84%
“…It has been hypothesised that the serological switching and genetic diversity of strains between pandemics and epidemics may be influenced by climate variations, with global warming making the environment favourable for cholera outbreaks by switching of virulence factors. This hypothesis is supported by studies of V. cholerae outbreaks in India [9], Bangladesh [10] and China [11], as well as a literature review of the influence of environmental factors on V. cholerae presence [12]. Furthermore, experimental studies have demonstrated variation with changes in environmental conditions in expression of ChiA2 and TfoX, key regulators of V. cholerae horizontal gene transfer [13].…”
Section: Introductionmentioning
confidence: 78%